PENINGKATAN STRATEGI PEMASARAN AGRIBISNIS STROBERI DI PURBALINGGA MELALUI DIGITAL MARKETING DAN PEMBERDAYAAN PETANI LOKAL - Suwali, Suwali; Wahyuni, Dewi (ICON Publisher, 2025)
This community service program aims to improve the competitiveness of strawberry farmers in Purbalingga through the implementation of digital marketing strategies. The main problems faced by farmers are dependence on conventional marketing, low digital literacy, and limited access to wider markets. This activity is carried out through intensive training and mentoring related to the use of social media, marketplaces, product branding, and digital-based business management. The results of the community service show a significant increase in farmers' skills in utilizing digital technology for marketing. Several farmers have started to actively use platforms such as Instagram, Facebook, and marketplaces to sell their products, which has an impact on increasing market reach and sales. In addition, innovation in packaging and product diversification has also encouraged an increase in the added value of strawberries. However, this program has limitations, such as differences in digital literacy levels and limited technological infrastructure. Therefore, further mentoring and support from the government and related institutions are needed to ensure the sustainability of digital transformation in agribusiness. With this program, it is hoped that strawberry farmers in Purbalingga can be more independent in managing their businesses and improve their welfare through more innovative and effective marketing.